Impression Management in Indonesia: Critical Analysis and Areas for Future Research - Santoso, Arif; Aryani, Y. Anni; Setiawan, Doddy (Universitas Negeri Malang, 2023)
This study aims to provide empirical evidence on the development of impression management research in Indonesia. This study analyzed thirty-four articles on impression management from eighteen nationally accredited journals Sinta 2 during the 2013-2023 observation period. Our articles are analyzed and classified based on topics, financial performance factors, and non-financial performance factors. Then we use a method with a field charting approach. This study found that financial performance factors such as company size, ROA, earnings management, and leverage are used more often than non-financial performance factors such as board size, corporate governance, economic conditions, company age, and analyst coverage. On the other hand, non-financial performance variables are more developed than financial performance as indicated by the variety of variables used. Form a causal model of financial performance and non-financial performance with full impression management using the additive model. We also found that impression management has a relationship with debt costs, agency costs, investment decisions, audit fees, trust, and market reactions. This implies that impression management is used to intervene in company costs. In addition, several variables show inconsistent results and need to be studied further to find these inconsistencies.